(3dZI GdLSO aj JShjb GdNOeGJs - (3GdaVd(B, (3eDjO YHO GdMSjfs; (3GdTcQj, HTQi TGcQs; (3GdWGFj, MejO YHO GdfHjs ((3YeGfs (3EHUGQ fGTQhf hehRYhf s, 2022)
(3eaGgje YGeg aj JShjb GdNOeGJ GdeUQajI, JShjb GdNOeGJ, JShjb GdNOeGJ aj Xd GOGQI GdhbJdG hUaha GdGfJXGQ, dZI GdLSO, eaghegG, GdGfaYGdGJ GdSHYI GdYGeI hGdCNWGA GdNeSI aj dZI GdhLg, JShjb GdPGJ hGdJShjb GdTNUj dQLd GdHjY Ydi CSGS dZI GdLSO, eaghe QLd GdHjY GdPj jJbf dZI GdLSO hCgejJg aj GdJShjb, dZI GdLSO aj JShjb GdNOeGJ GdSjGMjI, GdefJL GdSjGMj hGdNOeI GdSjGMjI, ehGUaGJ GdefJL GdSjGMj, GdSjGMI hCfhGYgG, GdCfTWI GdSjGMjI GdCSGSjI, GSJbWGH GdRHhf GdSjGMj hab efXhQ dZI GdLSO, MQcGJ HbjI CLRGA GdLSe hJhXjagG dJShjb GdNOeGJ GdSjGMjI, JYGed QLd GdHjY aj GdehbY GdSjGMj eY GdRHhf GdZGVH, dZI GdLSO aj JShjb GdNOeGJ GdeUQajI hGdeGdjI, JShjb GdNOeGJ GdeUQajI, fTCI fXQjI JShjb GdNOeGJ GdeUQajI, JWhQ GdNOeGJ GdeUQajI, GSJQGJjLjI JShjb GdNOeGJ GdeUQajI, CgOGa hCgejI GdJShjb GdeUQaj, echfGJ GdeRjL GdJShjbj GdeUQaj, egGe hhGLHGJ GOGQI GdJShjb GdeUQaj, dZI GdLSO aj JShjb GdNOeI GdeUQajI, UaGJ ebOe GdNOeI GdeUQajI GdfGLM, GTGQGJ dZI GdLSO GdeSJNOeI aj JShjb GdNOeI GdeUQajI, CNWGA dZI GdLSO YfO JbOje GdNOeGJ GdeUQajI, eTcdGJ JQJjH ehGbY JShjb GdNOeGJ, GdMGdGJ GdYTQI ddZI GdLSO aj JShjb GdNOeGJ GdeUQajI, GTGQGJ GdjO aj GdHhQUI dJShjb GdNOeGJ GdeGdjI, dZI GdLSO aj JShjb GdNOeGJ GdWHjI hGdEfSGfjI (B((3GdUe hGdHce(B)(3, dZI GdLSO aj JShjb GdNOeGJ GdJYdjejI hGdJQHhjI, GdMGdGJ GdNGUI aj JShjb GdNOeGJ HGdYJeGO Ydi dZI GdLSO(B.s
Keywords: (3GdJShjbs; (3GdJShjb(B- (3NOeGJ GdeYdheGJs